Genome wide association studies analysis of the natural ability of uptaking the phosphate in Vietnamese rice landraces - Phuong Nga, Mai Thi; Quoc Khang, Le; Quynh Anh, Chu Thi; Mai Huong, To Thi (Vietnam Journal of Biotechnology, 2021)
Phosphorus is the one of the most important macro-elements for the growth, development as well as productivity of plants. However, the overuse of fertilizer negatively affects soil and water quality, and the run-out of natural phosphates (Pi). Therefore, it is necessary to study on Pi cycle and find out the way to use Pi efficiently for rice as well as other crops. In this work, genome wide association studies (GWAS) was used to investigate the diversity in uptaking phosphate of 157 Vietnamese rice cultivars in order to find genes involved in this process. Rice plants were grown in sand columns and irrigated with Yoshida nutrient medium every three days during 6 weeks. The experiment was conducted with three repetations in a randomized complete block design. The natural ability of uptaking the phosphate was then quantified and evaluated. GWAS analysis was conducted using the Mix Linear Model that combine both kinship and population architechture of the panel with 6 Principale Component as co-factors. Results obtained from the association mapping revealed a total of 19 important single nucleotide polymorphism (SNPs), 9 quantitative trait locus (QTLs) and 22 genes. The obtained findings may provide genetic tools for the development of rice varieties which can use phosphate effectively.